Papillary muscle and left ventricular trabecular calcification in rheumatic mitral stenosis - Kumar, Rohit; Mangukia, Chirantan; Geelani, Muhhamed Abid (International Journal of Research in Medical Sciences, 2017)
Calcification of mitral valve apparatus in rheumatic pathology is not uncommon but isolated papillary muscle calcification and surrounding trabeculation is very rarely seen. Here valve leaflets and annulus are not calcified. This signifies the involvement of other factors in initiation of calcification other than rheumatic scarring. It may be chronic ventriculopathy that leads to trabecular calcification which involves papillary muscle and may later involve annulus. Clinical significance is that in high risk cases balloon mitral valvuotomy can be given a chance rather than replacement of valve as annulus and leaflets are pliable.